The Serious Challenge of Occult Hepatitis B Virus Infection-Related Hepatocellular Carcinoma in China - Xia, Renxiang; Peng, Jing; He, Jian; Jiang, Ping; Yuan, Chunyan; Liu, Xiaoli; Yao, Yunqing (Frontiers in Microbiology, 2022)
Background: It is unknown how many people in China have chronic occult hepatitis B virus (HBV) infection (OBI) (chronic HBV infection with negative serum hepatitis B surface antigen (HBsAg) (N-HBsAg)). Their clinical and virological characteristics, especially the correlation between the OBI and hepatocellular carcinoma (HCC), are still elusive and need to be investigated, including prevention, early diagnosis, and treatment strategies. Methods: 138 patients with HCC related to OBI were screened from 698 patients of HCC associated with HBV infection, their characteristics of epidemiology, clinical, biochemistry, virology, diagnostics, and therapeutics were analyzed retrospectively. Results: 19.8% (138/698) of patients with HBV-related HCC were OBI, of which 79.7% (110/138) were male, and 20.3% (28/138) were female. Most of the patients with OBI-related HCC were older men, and the median age was 63.2 years. 78.3% (108/138) of the patients had apparent right upper abdomen discomfort and/or pain and then sought medical examination. 21.7% (30/138) of the patients were identified by health examination. 10.9% (15/138) of the patients were admitted with chronic infection of HBV. 2.2% (3/138) of the patients were admitted with a family history of hepatitis B. The alpha-fetoprotein (AFP) serum-positive rate was 39.1% (54/138). Tumor lesions >5.0 cm, with intrahepatic and/or extrahepatic metastasis, were found in 72.5% (100/138) of the patients. The diameter of the tumor in the Group of hepatitis B core antibody-positive (HBcAb(+)) and hepatitis B surface antibody-positive (HBsAb(+)) was 7.03 ± 3.76 cm, which was much smaller than 8.79 ± 4.96 cm in the Group of HBcAb(+) and HBsAb(-) (P=0.035). Conclusion: It is estimated that at least 21 million OBI patients live in China. HBcAb(+) was not only the evidence of chronic HBV infection but also a dangerous mark for all the surface antigen-negative patients. A semi-annual or annual medical checkup was essential for all the OBI patients to identify HCC as early as possible. The hypothesis underlying our analysis was that hepatitis B surface antibody would prevent the progress of HCC and facilitate the clearance of HBV in patients with OBI. Thereby, the hepatitis B vaccine could be used to prevent severe disease consequences.